Education for sustainable healthcare: Leadership to get from here to there. (2nd October 2020) - McKimm, Judy; Redvers, Nicole; El Omrani, Omnia; Parkes, Margot W.; Elf, Marie; Woollard, Robert
Abstract: The current global crises, including climate, COVID-19, and environmental change, requires global collective action at all scales. These broad socio-ecological challenges require the engagement of diverse perspectives and ways of knowing and the meaningful engagement of all generations and stages of personal and professional development. The combination of systems thinking, change management, quality improvement approaches and models, appreciative/strength-based approaches, narratives, storytelling and the strengths of Indigenous knowledges, offer synergies and potential that can set the stage for transformative, strengths-based education for sustainable healthcare (ESH). The need for strong leadership to enact a vision for ESH is outlined here with the intent to enable and nurture the conditions for change, ultimately improving health and well-being across generations.